Pengembangan LKPD berbasis Teks Argumentatif melalui Inovasi Pembelajaran menggunakan Platform Gather Town di Masa Pandemi - Suaedi, Hasan; Fatqurhohman, Fatqurhohman (BELAJAR BAHASA: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2022)
The use of argumentative text-based worksheets using the gather two platform is believed to be able to help students in learning. This study aims to develop LKPD based on the argumentative text of Toulmin's model. In addition, the use of gather town is believed to motivate students in learning. The research method used is research and development (R&D). The development stage in this research starts from the development design. The second stage in this development is the expert validity test. Then the last stage is product testing. In this research, there are two stages of development. First, at the stage of the definition results, there are three aspects that have been carried out, namely problem identification, results of identification of LKPD objectives, results of student character identification, and results of problem solving identification. Second, at the design stage, it results in the development of LKPD based on argument text and instructions for using the gather town platform. Then at the trial stage of LKPD based on argumentative text using the gather town platform the researchers carried out several trial stages including (a) the expert validation stage consisting of validation of language learning experts and validation of educational technology experts, (b) the practicality stage consisting of practicality assessments of teachers and students. , and (c) the last stage is an assessment of the application of LKPD based on argumentative text to students.